Full-Array Boolean Logic CIM Macro With Self-Recycling 10T-SRAM Cell for AES Systems - Li, Xin; Pan, Ying; Jin, Qian; Chen, Lintao; Lou, Yang; Wu, Baofa; Long, Jiajun; Zhou, Yongliang; Peng, Chunyu; Wu, Xiulong; Lin, Zhiting (IEEE transactions on very large scale integration (VLSI) systems, 2025)
Computing in memory (CIM), which alleviates the need to transfer a large amount of data between processor and memory, significantly reducing latency and energy consumption, is a promising new computing architecture for addressing the von Neumann bottleneck problem. This article proposes a CIM array structure composed of self-recycling 10T static random access memory (SRAM) cells, which can realize orthogonal data writing, and multiple Boolean logical operations for the entire array. The self-recycling and full-array activation characteristics are extremely suitable for accelerating diverse data processing algorithms such as the Advanced Encryption Standard (AES). A 4-kb SRAM is implemented in 55-nm CMOS technology to verify the effectiveness of the design. Compared with other state-of-the-art architectures, the throughput and the operating frequency of the proposed CIM macro are increased to 843 GOPS/kb ( 2.64× ) and 823.7 MHz ( 2.6× ), respectively. The energy efficiency reaches 246.9 TOPS/W. When applied to the AES, the energy consumption is 35.77% less than the digital CIM architecture that is not self-recycling.